A single-cell-gap transflective liquid crystal display with a vertically aligned cell. Issue 8 (21st June 2019) - Wang, Qiong-Hua; Chu, Fan; Dou, Hu; Tian, Li-Lan; Li, Rui; Hou, Wen-Yi
ABSTRACT: A single-cell-gap transflective liquid crystal display with a vertically aligned cell using square ring electrode is demonstrated. The top substrate has a top planar common electrode, a square ring pixel electrode is coated on the bottom substrate, while a bumpy reflector is coated under the bottom substrate. In this device, the planar common electrode and square ring pixel electrode generate a strong longitudinal electric field in the transmissive region (T region) and a weak fringe field in the reflective region (R region). As result, the T and R regions accumulate the same optical phase retardation. The simulation results show that the display exhibits reasonably low operating voltage, high transmittance and well-matched voltage-dependent transmittance and reflectance curves. Besides, fabrication process of the transflective liquid crystal display is very simple. Graphical Abstract: